2021
DOI: 10.1186/s12889-021-11540-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 quarantine on dietary habits and physical activity in Saudi Arabia: a cross-sectional study

Abstract: Background The COVID-19 pandemic has forced governments around the world to impose strict hygiene and national lockdown measures, which in turn has changed the dietary and lifestyle habits of the world’s population. Thus, the aim of this study is to evaluate whether dietary and physical activity behaviors of Saudi Arabia’s adult population changed during the COVID-19 quarantine. Methods An electronic questionnaire which assessed changes in body wei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 30 publications
12
44
1
Order By: Relevance
“…Moreover, the Kingdom has also experienced both complete and partial lockdowns between March and June 2020 to mitigate the coronavirus disease 2019 (COVID-19) pandemic. Consequently, this inevitably limited physical activity [ 34 ]. These two factors were expected to contribute to the pre-existing obesity endemic in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Kingdom has also experienced both complete and partial lockdowns between March and June 2020 to mitigate the coronavirus disease 2019 (COVID-19) pandemic. Consequently, this inevitably limited physical activity [ 34 ]. These two factors were expected to contribute to the pre-existing obesity endemic in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is impacting many aspects of people’s food consumption behavior. In terms of snacking, many studies have reported significant changes in snacking frequency and behavior during COVID-19 [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. The nutritional composition of food is closely related to consumers’ food choice motives [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown favorable changes in individuals' eating habits, with an increase in the number of meals prepared and consumed at home [3][4][5]. Favorable effects were accompanied by other negative ones, such as an increase in alcohol consumption [4], increased "comfort food" consumption due to emotional distress [5], and reduced sleep quality [6]. These changes were accompanied by a more sedentary lifestyle due to increased screen time [7], smart working and the resultant abolition of walking or public transport to work [8], and fewer opportunities for practicing physical activity [9].…”
Section: Introductionmentioning
confidence: 99%
“…These changes were accompanied by a more sedentary lifestyle due to increased screen time [7], smart working and the resultant abolition of walking or public transport to work [8], and fewer opportunities for practicing physical activity [9]. Most studies have evaluated the short-term effects of social distancing and home isolation [5][6][7][8][9]. However, there is a lack of studies assessing the long-term effects of quarantine periods.…”
Section: Introductionmentioning
confidence: 99%